The Effectiveness of Kindness Intervention for Promoting Positive Emotions and Reducing Depressive Symptoms in Mexican Adults - Jorge Palacios-Delgado; Marcos Ambriz-Flores; Daniela Judith Cruz-Vargas (Social Sciences)
Background: In recent years, research has noted that depression is a prevalent mental health problem worldwide, including in Mexico among adults. Psychological interventions, such as those based on kindness, have shown promise in reducing depressive symptoms. However, there is little research in cultural contexts such as Mexico. In this context, the objective of the present research was to evaluate the preliminary efficacy of a brief intervention of performing kind acts (amabilidad) to increase happiness level as well as positive affect and reduce negative affect and depression symptoms among Mexican adults. Methods: A feasibility study was carried out with a pre-post intervention design with a control group of Mexican adults. The study used validated scales to measure happiness, positive and negative affect, and depression symptoms before and after the intervention. Participants received a brief intervention that included exercises to write expressions of kindness and practice acts of kindness towards themselves and others. Results: Preliminary results suggest that the kindness-based intervention produced improvements in their happiness, decreases in negative affect, and a significant reduction in depression symptoms compared to baseline levels and the control group. Conclusions: The findings of this study support the feasibility and potential effectiveness of kindness-based interventions to reduce depressive symptoms in Mexican adults.